Framing ESG investment commitments: A conceptual KAP model for sustainable financial literacy and attitudes among young investors in Malaysia - Mohamad Yusof , Nurul Afidah; Anthonysamy, Lilian; Hui, Lim Wen; Wen, Lau Yi; Ho, Loi Kwong; Fong, Bryan Ng Kai (Journal of Islamic, Social, Economics and Development, 2025)
Investing has evolved beyond mere capital generation, wealth accumulation, and income production for institutional and individual investors. By incorporating the environmental, social, and governance (ESG) considerations into its strategies, investment now increasingly serves as a means to contribute to societal and environmental enhancement while pursuing financial returns. Based on the Knowledge, Attitudes, and Practices (KAP) model, this paper presents a conceptual framework to understand ESG investment commitment among young investors in Malaysia. The KAP model provides a structured lens to uncover the cognitive and psychological factors influencing responsible investment decisions by examining the interrelationships among sustainable financial literacy (K), attitudes toward ESG (A), and ESG-aligned investment behaviour (P). The proposed methodology involves primary data collection using self-administered questionnaire, to be distributed to young investors aged 21 – 40 in the central region of Malaysia. This study yields practical insights into the current state of ESG investment commitment among young investors, highlighting the potential need for unique approach and tools in designing ESG-aligned financial literacy programs by the policymakers, financial institutions, and investment platforms.